2019
DOI: 10.1038/s41398-019-0664-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid oxidative stress metabolites in patients with bipolar disorder and healthy controls: a longitudinal case-control study

Abstract: Bipolar disorder (BD) is a mental disorder characterized by recurrent relapses of affective episodes, cognitive impairment, illness progression, and reduced life expectancy. Increased systemic oxidatively generated nucleoside damage have been found in some neurodegenerative disorders and in BD. As the first, this naturalistic prospective, longitudinal follow-up case-control study investigated cerebrospinal fluid (CSF) oxidative stress markers 8-oxo-7,8-dihydroguanosine (8-oxoGuo) and 8-oxo-7,8-dihydro-2′-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Several biological mechanisms have been proposed as potential underlying causes of BD. These include mitochondrial dysfunction (Jeong et al, 2020;Kato, 2017;Scaini et al, 2021;Scaini et al, 2016), oxidative stress (Knorr et al, 2019;Steullet et al, 2018), and neurotransmitter disruption (Liu, Zhao, & Guo, 2018;Martino & Magioncalda, 2021). Increasing numbers of genetic, biological, and neuroimaging studies have begun to address these hypotheses in recent years.…”
Section: Mechanisms and Pathophysiology Of Bdmentioning
confidence: 99%
“…Several biological mechanisms have been proposed as potential underlying causes of BD. These include mitochondrial dysfunction (Jeong et al, 2020;Kato, 2017;Scaini et al, 2021;Scaini et al, 2016), oxidative stress (Knorr et al, 2019;Steullet et al, 2018), and neurotransmitter disruption (Liu, Zhao, & Guo, 2018;Martino & Magioncalda, 2021). Increasing numbers of genetic, biological, and neuroimaging studies have begun to address these hypotheses in recent years.…”
Section: Mechanisms and Pathophysiology Of Bdmentioning
confidence: 99%
“…Several biological mechanisms have been proposed as potential underlying causes of BD. These include mitochondrial dysfunction (Jeong et al, 2020;Kato, 2017;Scaini et al, 2021;Scaini et al, 2016), oxidative stress (Knorr et al, 2019;Steullet et al, 2018), and neurotransmitter disruption (Liu, Zhao, & Guo, 2018;Martino & Magioncalda, 2021). Increasing numbers of genetic, biological, and neuroimaging studies have begun to address these hypotheses in recent years.…”
Section: Mechanisms and Pathophysiology Of B Dmentioning
confidence: 99%
“…Furthermore, magnetic resonance spectroscopy (MRS) studies in BPAD patients revealed lower levels of the mitochondrial-deriving amino acid N-acetyl aspartate (NAA) in the hippocampus and PFC ( Yildiz-Yesilogu and Ankerst, 2006 ; Frey et al, 2007 ), increased brain lactate ( Machado-Vieira et al, 2017 ), and alterations in phosphocreatine ( Kato et al, 1994 ), creatine kinase reaction rate constant ( Du et al, 2018 ), and ATP levels after stimulation ( Yuksel et al, 2015 ). Further observations include evidence of systemic impairment in mitochondria-dependent energy production in BPAD patients [reviewed in Nierenberg et al (2013) ], including reduced intracellular pH and higher plasma lactate levels ( Kato and Kato, 2000 ; Machado-Vieira et al, 2017 ; Jeong et al, 2020 ), higher levels of cerebrospinal fluid oxidative stress markers ( Knorr et al, 2019 ), increased lipid peroxidation and DNA/RNA oxidative damage, and higher levels of nitric oxide ( Brown et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%